The reclining nude : Agnès Varda, Catherine Breillat, and Nan Goldin - Wilson, Emma, 1967- (Contemporary French and francophone cultures ;, 2019)
This book, a sensuous evocation of images of the reclining nude, claims a female-identified pleasure in looking. Agnès Varda, Catherine Breillat, and Nan Goldin are re-imagining images of female beauty, display, (auto)eroticism, and intimacy. The reclining nude is compelling, for female-identified artists in the ethically adventurous, politically complex feminist issues it engages.